The Effect of Thin Capitalization, Supply Chain and Earnings Management on Economy development: Indonesia Evidence - Firmansyah, Amrie; Falbo, Teza Deasvery (International Journal of Supply Chain Management, 2020)
Abstract- This study aims to examine the effect of thin capitalization, supply chain and earnings management on economy development. The samples used in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2013-2015. Using purposive sampling, selected samples are 90 companies, so the total sample in this study is 270 observations. The examination method employed is the multiple linear regression analysis of panel data. The result of this study suggests that thin capitalization is positively associated with economy development, which indicates that manufacturing companies listed on IDX tend to use more debt than equity for funding its business to avoid taxes. While transfer pricing, aggressiveness, and supply chain management are associated with economy development. Furthermore, earnings management is positively associated with economy development indicates that earnings management could be conducted simultaneously with economy development